2002
DOI: 10.4049/jimmunol.168.2.671
|View full text |Cite
|
Sign up to set email alerts
|

UL16-Binding Proteins, Novel MHC Class I-Related Proteins, Bind to NKG2D and Activate Multiple Signaling Pathways in Primary NK Cells

Abstract: The UL16-binding proteins (ULBPs) are a novel family of MHC class I-related molecules that were identified as targets of the human CMV glycoprotein, UL16. We have previously shown that ULBP expression renders a relatively resistant target cell sensitive to NK cytotoxicity, presumably by engaging NKG2D, an activating receptor expressed by NK and other immune effector cells. In this study we show that NKG2D is the ULBP counterstructure on primary NK cells and that its expression is up-regulated by IL-15 stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
186
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(190 citation statements)
references
References 40 publications
(59 reference statements)
3
186
0
1
Order By: Relevance
“…ULBP-1 and MICA) induces CD25 expression, cytokine secretion and proliferation. Previous studies also reported the effect of soluble recombinant ULBP on the induction of GM-CSF and IFN-+ production by activated NK cells [3,27].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…ULBP-1 and MICA) induces CD25 expression, cytokine secretion and proliferation. Previous studies also reported the effect of soluble recombinant ULBP on the induction of GM-CSF and IFN-+ production by activated NK cells [3,27].…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, the binding of MICA and ULBP-1 to NKG2D-DAP10 and to an activating receptor complex that includes ITAM-bearing adaptors would reconcile the fact that triggering of the NKG2D-DAP10 complex by specific mAb is insufficient to induce IFN-+ secretion in human and mouse NK cells [12][13][14]21], while stimulation with NKG2D ligands induces IFN-+ secretion in human NK cells [3,27]. Yet, one should take into account that anti-NKG2D mAb abolish the binding of MICA-Fc and ULBP-Fc to NK cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in binding affinities to NKG2D have been reported for both mouse and human NKG2D ligands [34][35][36]. It has been proposed that molecular competition for receptor binding may exist between NKG2D ligands, with one ligand being favoured over another by NKG2D, due to more favourable binding kinetics [35].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular domains of NKG2D ligands share as little as 20-25% sequence identity [33]. In mouse and human different NKG2D ligands have been reported to have different affinities of binding to NKG2D [16,[34][35][36], although it is unknown whether this translates into functional differences in NK-cell stimulation. NKG2D ligands also differ in the nature of their association to cell membranes; some NKG2D ligands are glycosyl-phosphatidylinositol (GPI)-anchored to membranes, whereas others have transmembrane and cytoplasmic domains of variable length and sequence [9].…”
Section: Introductionmentioning
confidence: 99%